Perancangan Sistem Pandukung Keputusan Pemilihan Perguruan Tinggi Swasta Di Kota Semarang Dengan Metode AHP Untuk Siswa SMK Bina Negara Gubug - Laily Eka Andrianni; Danang Danang; Dani Sasmoko (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
The selection of universities has a very important role, at the end of school one of the problems often faced by students is determining where to continue the next level of education, including high school students, they find it difficult to determine which colleges and fields of study they will be capable of. Universities including private universities in the city of Semarang are increasingly making it difficult for students to determine private universities according to their criteria considering the difficulty of selection to enter public universities, in terms of quality or accreditation from these private universities, tuition fees, campus location close to boarding houses, places to eat, markets and a safe and conducive environment that supports them throughout their lives to study, distances that are easily accessible by private vehicles or public transportation, even the facilities obtained on campus are in accordance with the costs incurred or not, there are There are several criteria that are considered when choosing a private university.AHP is a decision support model developed by Thomas L. Saaty. This decision support model will describe a multi-factor problem or complex criteria into a hierarchical form. The AHP method is precise and systematic in the decision-making process according to the criteria set by Kopertis 6 based on data analysis. The research method used is R&D. Research and Development method is research that is used to produce certain products and test the effectiveness of these products. In this study the authors built a decision support system using the AHP method using 5 criteria (Cost, Facilities, Mileage, Quality, Location